In vivo Antioxidant and Lipid Peroxidation Effect of Various Extracts of Whole Plant of Mucuna pruriens (Linn) in Rat Fed With High Fat Diet - Satheesh Kumar, D.; Kottai Muthu, A.; Anton Smith, A.; Manavalan, R. (Asian Journal of Chemistry, 2010)
The present study was conducted to evaluate the in vivo antioxidant and lipid peroxidation effect of various extracts of whole plant of Mucuna pruriens (Linn). High fat diet rats showed significant decreased activities of tissue enzymatic and non enzymatic antioxidant. High fat diet induces the oxidative stress in cell by producing reactive oxygen species. Antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), non enzymatic antioxidant glutathione (GSH) and thiobarbituric acid reactive substance levels were increased in the administration of methanolic extract of Mucuna pruriens in high fat diet rats when compared to other two extracts. Hence it is concluded that methanolic extract of Mucuna pruriens were found to have protective action against high fat diet induced oxidative stress in different tissues in rats.